BETWEEN FEAR AND THE DESIRE TO BE ACCEPTED: SOCIAL ANXIETY AMONG WOMEN WHO USE SOCIAL MEDIA - Az-zahra Atika Putri; Zata Ismah (PEOPLE: International Journal of Social Sciences, 2026)
Social anxiety is a form of anxiety commonly experienced by individuals, especially during late adolescence and early adulthood. This developmental period is characterized by demands for social adaptation, independence, and identity search, which often cause excessive worry in social interactions. This study aims to determine the profile of social anxiety in late adolescent and early adult women. The method used was quantitative observational with a cross-sectional design. The study sample consisted of 155 female respondents aged 18–25 years in Palembang City, obtained through accidental sampling. The research instrument was a questionnaire that measured aspects of general feelings, physical feelings, and cognitive changes. The results showed that the majority of respondents were in the moderate category for all aspects, with a proportion of 58.7% in general feelings, 62.6% in physical feelings, and 75.5% in cognitive changes. The aspect of general feelings was the most vulnerable to being in the high category (30.3%). Based on age differences, late adolescents showed higher anxiety than early adults, particularly in terms of general feelings and cognitive changes. In conclusion, social anxiety in late adolescent to early adult women was generally moderate, with a higher tendency in the late adolescent group. These findings indicate the importance of psychological intervention to help individuals manage social anxiety according to their stage of development.